Colchicine for pericarditis due to COVID-19: a case report - Patel, Parth; Patel, Sudhendu; Shah, Vidhi (International Journal of Advances in Medicine, 2022)
The pericardium is a fibroelastic sac made up of visceral and parietal layers separated by a (potential) space, the pericardial cavity.The most troublesome complication of acute pericarditis is the development of recurrent episodes of pericardial inflammation, occurring in 15% to 32% of cases. Therapeutic modalities are nonspecific and include non-steroidal anti-inflammatory drugs (NSAIDs) and corticosteroids. Here we present a case of a patient presenting with pericarditis due to COVID-19. He was successfully treated with colchicine. To our knowledge acute pericarditis due to severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) might be an under diagnosed condition in this pandemic. We want to share our ﬁndings, given the urgent need for different diagnostic and therapeutic strategies in order to better manage COVID-19 patients, and diminish the SARS-CoV-2 complications.